2016
DOI: 10.1007/s10113-016-0980-9
|View full text |Cite
|
Sign up to set email alerts
|

Implications of future bioclimatic shifts on Portuguese forests

Abstract: As climate is an important driver of vegetation distribution, climate change represents an important challenge to forestry. We (1) identify prevailing bioclimatic conditions for 49 relevant forest species in Portugal and (2) assess future shifts under climate change scenarios. We compute two bioclimatic indices (aridity and thermicity) and a new composite index, at *1 km spatial resolution, and overlap with the species' current ranges. Locations are based on a digital inventory, while climate parameters for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 55 publications
5
46
0
Order By: Relevance
“…The bioclimatic classification plays a relevant role in establishing relationships between ecosystems and climate (Del‐Arco et al ., 2002; Mesquita and Sousa, 2009; Cano et al ., 2012; Torregrosa et al ., 2013; Pesaresi et al ., 2014; Aguilera et al ., 2015; Monteiro‐Henriques et al ., 2016). On a regional scale, this assessment allows a better understanding of the impact of climate change in the agroforestry systems (Costa et al ., 2017; del Río et al ., 2018). The Worldwide Bioclimatic Classification System (WBCS) establishes relationships between the worldwide vegetation types and several quantitative bioclimatic indexes.…”
Section: Introductionmentioning
confidence: 99%
“…The bioclimatic classification plays a relevant role in establishing relationships between ecosystems and climate (Del‐Arco et al ., 2002; Mesquita and Sousa, 2009; Cano et al ., 2012; Torregrosa et al ., 2013; Pesaresi et al ., 2014; Aguilera et al ., 2015; Monteiro‐Henriques et al ., 2016). On a regional scale, this assessment allows a better understanding of the impact of climate change in the agroforestry systems (Costa et al ., 2017; del Río et al ., 2018). The Worldwide Bioclimatic Classification System (WBCS) establishes relationships between the worldwide vegetation types and several quantitative bioclimatic indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Vineyards [22]. Portuguese vineyards are thus currently growing under a wide range of thermal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Under future climatic conditions, we projected that the range of the ginkgo would shift northward and upward. Many studies support this finding, speculating that plants will move to higher altitudes and high latitudes due to global warming (Costa et al 2017;Innes 1991;Winkel et al 2015). Studies have also shown that temperate and cold temperate trees may grow faster in moderate warming conditions (Davis and Shaw 2001;Norby and Luo 2004;Peltola et al 2002;Ruiz-Labourdette et al 2015).…”
Section: Future Projections and Management Implicationsmentioning
confidence: 93%